Evidance Based Pracrice Penerapan Senam Otak Terhadap Fungsi Kognitif Pada Pasien - Molintao, Winarsi; Damiti, Muhammad Olis (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Dementia is a symptom of decreased memory, thinking ability, behavior, and the ability to perform daily activities. Brain gymnastics is a series of simple body movement exercises performed to stimulate the left and right brain (lateral dementia), lighten or relax the front or back of the brain (focusing dementia), and stimulate the systems related to feelings or emotions, namely the midbrain (limbic) and cerebrum (concentration dementia). The purpose of this study was to determine the Application of Brain Gymnastics on Cognitive Function in Patient Mrs. R with Dementia in a Nursing Home. The research method used was a descriptive type of research with a case study design, using a nursing process approach. The results of the study were the main diagnosis of Memory Disorders related to the aging process characterized by having experienced forgetfulness. Interventions were given 2x24 hours. Based on the development of the patient's condition during the 2 days of brain gymnastics, the results obtained were that the patient said she felt she could gradually recognize the day, month, and year. In conclusion, the implementation of Brain Gymnastics after nursing intervention has been shown to improve memory, although the desired outcome has not yet been achieved, necessitating continued intervention. One recommendation is the need for greater attention to dementia patients by regularly performing brain gymnastics.